Himatanthus Willd. ex Schult. (Apocynaceae): Review - Soares, Fabiana P.; Cavalcante, Larissa F.; Romero, Nirla Rodrigues; Bandeira, Mary A. M. (Pharmacognosy Reviews)
The genus Himatanthus Wild. ex Schult. (Apocynaceae) includes about 13 species and five subspecies widely distributed in South America, especially Brazil. The phytochemical reports on this genus have revealed mainly triterpenes and iridoids. The plants are traditionally used as anthelmintic, antitumor, and antiinflammatory agents. The most used parts of the plant are its bark, leaves, and latex. This review emphasizes the phytochemical constituents and medicinal properties, which may help in future research. The research was conducted with data obtained from books about medicinal plants, theses, dissertations, and articles in refereed journals.
Keywords: Biological effects; botanical; ethnopharmacology; folk medicine; Himatanthus; phytochemistry